EFFECT OF A 12-WEEK SUBMAXIMAL RESISTANCE TRAINING IN THE LOWER LIMB STRENGTH IN ELDERLY FEMALE POPULATION (Fiep Bulletin - online, 2014)
One of the main problems related to the aging process is the progressive decrease in functional. The resistance training (RT) seem to be the essential part and maybe even priority in the exercise prescription for the elderly, since it can stimulate the maintenance of the muscular strength. The purpose of this study was to verify the effect of 12 weeks of sub maximum resistance training (submaxRT) in the lower limb strength in female elderly. Participated in the study 6 elderly women with 6 months of experience in resistance exercise practice, who were executing RT 3 times a week, in 50-minute sessions. The exercises used to assess the strength were the Leg Press 45º (LP) and the Leg Extensor Bench (LEG). The first load per repetition test (12 MR) was executed on the first session of exercises (12 RM). On the 5th week another test was executed to ensure the sub maximum training. The load values found were 86 (±26) kg for the LP and 7 (± 2,7) kg for the LEB, which respectively corresponded to 81,13% and 71,43% of the load in the initial 12 MR test. The final test was executed after 12 weeks of training. The results for the initial and final tests showed values of 102,5 (±47,7) kg and 147,5 (±45) kg for the LP and 10 (±4,1) kg and 14,2 (±4,3) kg for the LEB respectively. The t paired test showed that there is a significant difference (p=0,000) between the loads of the initial and final load tests in the LP, with a mean load increase of, 42±8,4 kg, which represents approximately 41% increasing and in the LEB (p=0,003), with a mean weight of 4±1,4 kg, which represents a difference of approximately 40%. The results show that there has been a significant increase, of 40% in the lower limbs strength in elderly women using a RT sub maximal protocol.
Keywords: Strength; Resistance Training; Elderly